2021
DOI: 10.26434/chemrxiv.14251649.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of Multi-Protein Complexes through Charge-Directed Sequential Activation of Tyrosine Residues

Abstract: Site-selective protein-protein coupling has long been a goal of chemical biology research. In recent years, that goal has been realized to varying degrees through a number of techniques, including the use of tyrosinase-based coupling strategies. Early publications utilizing tyrosinase from <i>Agaricus bisporus</i> showed the potential to convert tyrosine residues into <i>ortho</i>-quinone functional groups, but this enzyme is challenging to produce recombinantly and suffers from some li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…Previous work from our lab has shown that tyrosinase from Bacillus megatarium (megaTYR) is capable of oxidizing phenols to o-quinones that show excellent selectivity for free thiol additions. 26 We have demonstrated that megaTYR can be easily obtained through recombinant protein expression in Escherichia coli and maintains high levels of activity under proper storage conditions at −80 °C. 27 Furthermore, due to the size difference between the enzyme (∼35 kDa) and the antibody, purification with high-molecular weight cut off filters or size exclusion chromatography can be used for sample preparation.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous work from our lab has shown that tyrosinase from Bacillus megatarium (megaTYR) is capable of oxidizing phenols to o-quinones that show excellent selectivity for free thiol additions. 26 We have demonstrated that megaTYR can be easily obtained through recombinant protein expression in Escherichia coli and maintains high levels of activity under proper storage conditions at −80 °C. 27 Furthermore, due to the size difference between the enzyme (∼35 kDa) and the antibody, purification with high-molecular weight cut off filters or size exclusion chromatography can be used for sample preparation.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…11 With the generation of several megaTYR variants, our lab has been able to install negatively charged oligonucleotide cargo onto proteins site-specifically. 26 The D55R megaTYR variant has the strongest preference for negatively charge substrates and has been used to attach DNA to proteins. We explored the conjugation of murine and human TLR9 agonists�ODN1826 and ODN2006, respectively� using D55R megaTYR (Supplementary Figure S6).…”
Section: Bioconjugatementioning
confidence: 99%
“…This is necessary because proteins are generally present in low concentrations (1−100 μM) and are also large in size, rendering them sterically encumbered coupling partners. 18,19 However, in the case of protein−protein coupling reactions, it is generally not practical to use a larger stoichiometric excess of one partner. The protein−protein coupling problem arises because two of these sterically encumbered coupling partners, both present at low concentrations, must come together to form the desired protein−protein conjugate.…”
Section: The Protein−protein Coupling Problemmentioning
confidence: 99%
“…122 Further work explored the use of different tyrosinases to expand the scope of tyrosine residues that could be targeted in this manner. 19 A tyrosinase from Bacillus megaterium (megaTYR) was found to be more promiscuous and enabled the oxidation of tyrosine residues in a high number of sequence motifs, as assayed by peptide experiments. Further engineering of megaTYR led to a variant that displayed high activity toward tyrosine residues in the E 4 Y motif, ultimately enabling the construction of a linear triple-protein conjugate comprising nanoluciferase, GFP, and mCherry.…”
Section: Approaches Mediated By Tyrosine Oxidationmentioning
confidence: 99%
“…To modify the existing dTMV constructs at the S123(′)C position with a His-tag, we employed an oxidative coupling reaction using the enzyme tyrosinase for the conjugation of phenol-containing peptides, small molecules, or proteins to cysteine residues on protein surfaces (36)(37)(38). Short peptide sequences with a C-terminal tyrosine and an N-terminal His-tag were designed to conjugate to the dTMV double disks at S123(′)C and subsequently coordinate with nickelnitrilotriacetic acid (Ni 2+ -NTA) lipids in SLBs.…”
Section: Asymmetric Dual-functionalization Of Dtmv Allows Dye-labeled...mentioning
confidence: 99%